2019
DOI: 10.5093/pi2019a10
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Length of Residence and Geographical Origin on the Social Inclusion of Immigrants

Abstract: Migration is regarded as one of the most stressful events that people can experience that requires them to make major adaptive responses (Cakir & Guneri, 2011). The migratory process entails many simultaneous changes, which potentially have long-lasting effects (Achotegui, 2009; Teixeira de Almeida & Vaz, 2011). Migration has become an increasingly common process, and therefore intercultural adaptation processes are of increasing relevance (Barker, 2015; United Nations, 2015). Migration involves a breakdown of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 101 publications
1
11
0
2
Order By: Relevance
“…En las fuentes de procedencia del apoyo, las correlaciones más fuertes se sitúan en el plano de los amigos españoles, seguidos de los miembros de la familia. Estos resultados evidencian la especial importancia, en términos de satisfacción vital y sentido de comunidad, que supone para las personas inmigrantes contar con una red amplia de apoyo por parte de autóctonos para su integración y bienestar (Domínguez-Fuentes y Hombrados-Mendieta, 2012; Millán-Franco, Gómez-Jacinto, Hombrados-Mendieta, González-Castro y García-Cid, 2019).…”
Section: Discussionunclassified
“…En las fuentes de procedencia del apoyo, las correlaciones más fuertes se sitúan en el plano de los amigos españoles, seguidos de los miembros de la familia. Estos resultados evidencian la especial importancia, en términos de satisfacción vital y sentido de comunidad, que supone para las personas inmigrantes contar con una red amplia de apoyo por parte de autóctonos para su integración y bienestar (Domínguez-Fuentes y Hombrados-Mendieta, 2012; Millán-Franco, Gómez-Jacinto, Hombrados-Mendieta, González-Castro y García-Cid, 2019).…”
Section: Discussionunclassified
“…It would be also important to highlight in this study the length of residence in the host country. This variable leads to contradictory results: length of residence has been traditionally considered to relate to higher adaptation and well-being of the collective, thanks to acculturation strategies that would reduce the stress suffered by migrants (Millán-Franco et al, 2019c). However, new research suggests that the length of residence can have a negative impact in the well-being of migrants: for instance, migrants who acquire new habits from the native population and reduce their physical activity or change their diets.…”
Section: Introductionmentioning
confidence: 99%
“…The results on residence time are similar to those of other studies that have found an association between this factor and greater SWL in Latin American groups in Spain. This ethnic group is culturally closer to Spanish culture than other migrant groups and shows greater SWL (Millán‐Franco, Gómez‐Jacinto, Hombrados‐Mendieta, González‐Castro, & García‐Cid, 2019). In contrast, a negative association was found between older age and SWL, although this association was stronger in the Latin American group.…”
Section: Discussionmentioning
confidence: 99%
“…SS from native friends has also been highlighted as the network that best predicts SWL and integration in the host country (García‐Cid, Hombrados‐Mendieta, Gómez‐Jacinto, de las Olas Palma‐García, & Millán‐Franco, 2017). These differences in results have been explained by ethnic differences between study samples (Liang & Bogat, 1994), the frequency and availability of establishing relationships in the host country (García, Ramírez, & Jariego, 2002), working conditions and the legal status of migrant workers (Plaza et al, 2005), or time of residence in the host country (Millán‐Franco, Gómez‐Jacinto, Hombrados‐Mendieta, González‐Castro, et al, 2019). However, studies on SS and gender differences in the migrant population are scarce.…”
Section: Social Support Satisfaction With Life and Gender In The MImentioning
confidence: 99%